The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jnu.12553
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Workplace Incivility on Nurses’ Patient Safety Competence

Abstract: Purpose This study assessed clinical nurses’ workplace incivility experiences and determined the effects of workplace incivility experiences on nurses’ patient safety competence. Design This quantitative study surveyed 261 clinical nurses in two acute healthcare facilities in Saudi Arabia from June to August 2019. Methods A self‐administered survey, including the Nurse Incivility Scale and the Health Professional Education in Patient Safety Survey, was employed to assess the variables workplace incivility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 23 publications
7
53
1
2
Order By: Relevance
“…At times, CRCs' roles in advocating for patients, patients-turnedresearch-participants, and research may conflict, and coordinators must balance these roles within a large interprofessional team [46]. Previous research indicates that health care team relationships are critical to patient outcomes, and team relationship quality predicts patient mortality rates [47], treatment adherence [48], and patient safety [49]. Our data indicate that coordinators generally find support among their CRC colleagues.…”
Section: Discussionmentioning
confidence: 74%
“…At times, CRCs' roles in advocating for patients, patients-turnedresearch-participants, and research may conflict, and coordinators must balance these roles within a large interprofessional team [46]. Previous research indicates that health care team relationships are critical to patient outcomes, and team relationship quality predicts patient mortality rates [47], treatment adherence [48], and patient safety [49]. Our data indicate that coordinators generally find support among their CRC colleagues.…”
Section: Discussionmentioning
confidence: 74%
“…These found significant associations between unacceptable behaviour and the perceived frequency of errors,30 adverse events (such as medication errors, nosocomial infections and falls29 44) and near misses or negative outcomes 45. Three studies found either direct23 46 or indirect47 associations between the frequency of unacceptable behaviour and patient safety culture of their workplace, while a fourth study48 demonstrated an association with individual HCW safety competence.…”
Section: Resultsmentioning
confidence: 96%
“…The American Nurses Association de nes incivility as "one or more rude, discourteous, or disrespectful actions that may or may not have a negative intent behind them" [7]. These behaviors include sarcastic remarks, grinning, contemptuous tone of voice, hostile looks, interrupting others, shouting, spreading rumors, taking advantage of others' attempts and achievements, and ignoring authority and identity in front of colleagues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Incivility in the nursing profession can have signi cant consequences for nurses, patients, and health care organizations [14]. Nurses who are affected by such behaviors in their work environment may experience psychological and physiological distress [7] and problems such as low self-esteem, anxiety, fatigue, sleep disturbance, and depression [15]. Such behaviors can also lead to reduced quality of patient care, poor health outcomes in patients, increased medication errors [16], organizational con icts, burnout, increased job stress, deciding to quit nursing, declined organizational commitments, and weaker work performance [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation